Nitrogen-Doped MXene Electrodes for High-Voltage Window Supercapacitors in Organic Electrolytes - Yingyi Liao; Xiaoqing Bin; Jing Xu; Xuedong He; Wenxiu Que (Chemistry)
MXene has excellent electrochemical performance in aqueous electrolytes; however, its narrow voltage window (hydrolysis voltage ≤ 1.2 V) limits the energy density of supercapacitors. Compared to conventional aqueous electrolytes, ionic liquid (IL) electrolytes exhibit a much larger voltage window, but their larger ion size limits the transport and intercalation of IL cations in MXene electrodes. Therefore, the electrochemical performances for three different types of organic electrolytes based on nitrogen-doped MXene electrodes in supercapacitors were investigated, with the voltage windows of the devices effectively widened to 2.4 V. In addition, the nitrogen-doped MXene electrodes also effectively adjusted the interlayer spacing of the MXene nanosheets, with the enlarged interlayer spacing (from 12.60 Å to 14.24 Å) being more favorable for the intercalation and de-intercalation of larger-sized organic ions within the electrodes, thus effectively storing a charge. Among them, the 1 M EMIMTFSI/LiTFSI/ACN electrolyte is optimal due to the introduction of a smaller ion size for Li+, and so the corresponding supercapacitor achieves the electrode capacitance of up to 147 F g−1, with the maximum energy density of 29.4 Wh kg−1. This work provides a new strategy for reasonably optimizing the design of organic electrolytes matching modified MXene electrodes to effectively enhance the energy density of supercapacitors.